The social problems of families caring for their close relatives in the terminal stages of an illness - Piotrowska, Ewa Zofia (Medycyna Paliatywna/Palliative Medicine, 2015)
Introduction : Family is one of the most important human environments, supporting life and development. When one of the members falls ill the old lifestyle becomes disorganised. Psycho emotional equilibrium of relatives is shaken, ethical problems arise. Aim of the study: Pinpointing social problems of families looking after terminally ill relatives, their causes, family motivation for care, ways of managing crisis situations, carers’ support. Material and methods: The research included 10 main carers. Methodology – quality research, method – case study. Basic technique – an interview assisted by auxiliary observation. Tool – a questionnaire of in-depth interview. Results and conclusions : Carers for terminally ill encountered problems related to changes in the family functioning, emotional reactions, moral dilemmas. Disorganisation of family life included a change in the priorities: the ill and the carer becoming most important, shifting the weight of the problems and limiting social contacts. Emotional reactions of families showed fear of relative’s death, longing and suffering resulting from approaching loneliness. Moral dilemmas concerned the conversation with the ill about the negative outcome of the illness and the decision to place them in an institution. Problems arose due to external-situational and internal-psychological elements. Carers’ dominant motivation was love and closeness to the ill and also their upbringing and system of values of the family home. The ways of coping were intuitional strategies concentrated on the problem. Similar experiences from the past had a considerable influence. Carers expected support from other family members, friends and health service workers.